Average Error: 0.0 → 0.0
Time: 14.9s
Precision: 64
\[tx \cdot tx - \sqrt{ty}\]
\[tx \cdot tx - \sqrt{ty}\]
tx \cdot tx - \sqrt{ty}
tx \cdot tx - \sqrt{ty}
double f(double tx, double ty) {
        double r8157990 = tx;
        double r8157991 = r8157990 * r8157990;
        double r8157992 = ty;
        double r8157993 = sqrt(r8157992);
        double r8157994 = r8157991 - r8157993;
        return r8157994;
}

double f(double tx, double ty) {
        double r8157995 = tx;
        double r8157996 = r8157995 * r8157995;
        double r8157997 = ty;
        double r8157998 = sqrt(r8157997);
        double r8157999 = r8157996 - r8157998;
        return r8157999;
}

Error

Bits error versus tx

Bits error versus ty

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[tx \cdot tx - \sqrt{ty}\]
  2. Final simplification0.0

    \[\leadsto tx \cdot tx - \sqrt{ty}\]

Reproduce

herbie shell --seed 1 
(FPCore (tx ty)
  :name "tx*tx-sqrt(ty)"
  (- (* tx tx) (sqrt ty)))